PENGEMBANGAN METODOLOGI PEMBELAJARAN PAI: IMPLEMENTASI QUANTUM TEACHING DI SMPN KOTA BENGKULU - Alfauzan Amin (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2011)
AbstractThis study aims to describe: 1) The perception of teachers in the development of Islamic learning methodology by implementing Quantum Teaching in junior high school in Bengkulu 2) Development of Islamic learning methodologies by implementing Quantum Teaching in junior high school in Bengkulu. 3) factors supporting or inhibiting the implementation of religious teachers in the development of Islamic learning methodology by implementing Quantum Teaching in junior high school in Bengkulu. In line with the nature of the research, the research method used is qualitative method. Bogdan and Taylor (in Moeleong, 1996) defines